2015
DOI: 10.5620/eht.e2015008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a newsletter on bedding control on house dust mite allergen concentrations in childcare centers in Korea

Abstract: ObjectivesBedding in childcare centers (CCCs) can hold house dust mite (HDM) allergens. This study examined whether HDM allergen levels can be reduced through the distribution of an educational newsletter on bedding control to parents of CCC children in Korea.MethodsAll 38 CCCs were measured for Der 1 (sum of Der f 1 and Der p 1) concentrations on classroom floors and bedding before the intervention. Educational newsletters on children’s bedding control were sent to 21 CCCs by mail, and teachers were asked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Our reported study concentrations were less than the other reported measurements. When comparing the Der p 1 levels measured in our study with Der p 1 levels measured in international locations, our concentrations were comparable to the concentrations reported for childcare centers in parts of Europe, Oceania, and Asia (Poland (0.005–0.16 µg/g) [ 44 ], Sweden (<0.016–0.106 µg/g) [ 42 ], Germany (0.2 µg/g) [ 46 ], New Zealand (0.22 µg/g) [ 49 ], Singapore (0.3 µg/g) [ 35 ], and Korea (0.04 µg/g) [ 54 ]). For those locations where Der f 1 was measured, the results show that our reported concentrations (<0.012–0.09 µg/g) are comparable to concentrations reported for childcare centers in North Carolina (0.1 µg/g) [ 34 ], Germany (0.26 µg/g) [ 46 ], and Singapore (0.2 µg/g) [ 35 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our reported study concentrations were less than the other reported measurements. When comparing the Der p 1 levels measured in our study with Der p 1 levels measured in international locations, our concentrations were comparable to the concentrations reported for childcare centers in parts of Europe, Oceania, and Asia (Poland (0.005–0.16 µg/g) [ 44 ], Sweden (<0.016–0.106 µg/g) [ 42 ], Germany (0.2 µg/g) [ 46 ], New Zealand (0.22 µg/g) [ 49 ], Singapore (0.3 µg/g) [ 35 ], and Korea (0.04 µg/g) [ 54 ]). For those locations where Der f 1 was measured, the results show that our reported concentrations (<0.012–0.09 µg/g) are comparable to concentrations reported for childcare centers in North Carolina (0.1 µg/g) [ 34 ], Germany (0.26 µg/g) [ 46 ], and Singapore (0.2 µg/g) [ 35 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%